Leadership Style in TVET Education Towards 21st Century - Mohd Fikri bin Ismail; Sharifah Nurulhuda Tuan Mohd Yasin (LPPM NAROTAMA UNIVERSITY, Indonesia, 2020)
Leadership is a critical aspect in organisation. As in 21st century, it’s shown that there are stiff competitions between giant companies to dominate the world economy. Literature shows that their secret of success depends on an open and innovative leadership. Academic leadership should be changed literally to tackle the globalization challenges, in line with technological advances. Leaders can be considered as a goal-setter, advocator, initiator, communicator, supporter, coordinator, coach, evaluator, manager, information provider and role model while implementing changes within the organisation. This study aims to identify leadership style in TVET education by 21st century. The method used for the study is by analyzing and comparing the document with reference from previous review. Identification of theories that uphold leadership style will be the result of this study. This proves the connection between the theories used in this study.